Continuous liquid interface production of alginate/polyacrylamide hydrogels with supramolecular shape memory properties. (1st March 2020) - Huang, Bingxue; Hu, Rui; Xue, Zhouhang; Zhao, Jiangqi; Li, Qingye; Xia, Tian; Zhang, Wei; Lu, Canhui
Highlights: Alginate/polyacrylamide hydrogel is 3D printed by CLIP firstly. The CLIP-printed hydrogel presents excellent compressive properties. The CLIP-printed hydrogel shows rapid supramolecular shape memory properties. Abstract: A recently developed three-dimensional (3D) gel-printing technology, namely continuous liquid interface production (CLIP), was utilized to fabricate supramolecular shape memory hydrogels with high resolutions and complex 3D geometries. The UV-curable ink for CLIP was composed of hydrogel precursors (alginate and acrylamide) and a photo-initiator (ammonium persulfate). As expected, the double network formed from ionically crosslinked alginate and covalently crosslinked polyacrylamide endowed the printed hydrogels with excellent mechanical properties. Meanwhile, due to the reversible metal-ligand coordination interaction, the hydrogel could be temporarily immobilized into an optional shape after introducing calcium ions and return to its original shapes upon ion removal, exhibiting ion-triggered shape memory effect. Moreover, the presence of ions greatly improved the conductivity of the resultant hydrogels. Such 3D printed versatile hydrogels with complex geometries demonstrated the potential for selected applications, particularly in load-bearing materials and flexible electronic devices.